Science and Technology in The Islamic Perspective - Ahmad Dibul Amda (Institut Agama Islam Negeri (IAIN) Curup, 2016)
This article attempts to discuss Islamic concept on science and technology from the perspective of al-Qur’an. Islam through the Qur'anic verses as the primary source of its teaching strongly recommand human to use reason, observation, listening as much as possible through the assessment process which result in rational thought. The characteristics of Islamic science is integration of the potential of reasoning, mind and revelation, or remembering and thinking, so that sciences created by Muslim scientists would clearly reflect Islamic values, become meaningful and bring mercy for the universe. Key words: science, technology, al-Qur’an and Islam